Preparing Preservice Teachers to Manage Behavior Problems in the Classroom: The Feasibility and Acceptability of Using a Mixed-Reality Simulator. Issue 2 (June 2020) - Larson, Kristine E.; Hirsch, Shanna E.; McGraw, Jillian P.; Bradshaw, Catherine P.
Given the high percentage of new teachers who struggle with classroom management, preservice educators need more opportunities to develop their skills in managing challenging student behaviors prior to entering the classroom. There is growing interest in using mixed-reality simulators to provide educators opportunities to receive guided practice in implementing a variety of techniques, including classroom management strategies. Yet these technologies may be difficult for preservice programs to integrate into the curriculum and may be perceived as stressful for some student teachers. The current article presents findings from a feasibility and acceptability study of the TeachLive™ mixed-reality teaching simulator, which was used as a supplemental guided practice opportunity for preservice student teachers enrolled in classroom management and special education methods classes. Data from 62 preservice teachers suggest there is potential for acceptability among teachers in training, particularly if adjustments are made to reduce their stress and performance anxiety. Recommendations for using mixed-reality simulators in preservice training are provided.